Non-Blocking and Multi Wavelength Optical Router Design based on Mach-zehnder Interferometer in 3-D Optical Network on Chip - Sanaz Asadinia; Mahdi Mehrabi; Elham Yaghoubi (Majlesi Journal of Electrical Engineering)
Due to the increasing number of cores in a chip, electronic networks on chip cannot be an effective solution for using multi-core processors. The use of optical connection technology for networks on 3D chip is an ideal choice recommended in response to delay and reliability. In optical network architecture on 3D chip, 7-port routers are used to data transfer. The structure of the optical routers in the network on the 3D optical chip affects the Performance transmission of the entire network so that the provision of optical router with minimal loss and power consumption is considered by researchers in this domain. In this study, a seven-port Non-blocking optical router based on the Mach Zehnder interferometer optical switch in the network on a 3-D optical chip is presented. This router consists of 18 Mach Zehnder interferometer optical switches that can transfer multiple wavelengths concurrently. To evaluate the proposed 7-port router in the network on the 3D optical chip, the parameters of insertion loss, bandwidth density and power consumption are considered and the simulation results represent that this router decreases the loss as much as possible and improves the use of the wavelength channel comparing to available router and has the ability to transfer 4 wavelengths simultaneously with a wavelength range of 1525-1565 nm and a data transfer rate of 20Gbps for all 42 optical links. So it is useable for optical connection on the chip.